Purchasers' deliberations on psychosocial needs within the process of allocating healthcare services for older home-dwelling persons with dementia: a qualitative study - Anette Hansen; Solveig Hauge; Ragnhild Hellesø; Ådel Bergland (BMC, 2018)
Abstract Background Meeting psychosocial needs is a significant component of quality dementia care. To enable persons with dementia to live at home for as long as possible, a community healthcare service offering care where physical, social, psychological, cultural and spiritual needs are met, is recommended. A comprehensive allocation process is required to allocate individually tailored healthcare services. However, the allocation process for older home-dwelling persons with dementia, specifically for services to safeguard psychosocial needs, remains largely unexplored. Accordingly, this study aims to explore purchasers' deliberations on psychosocial needs during the process of allocating healthcare services to older home-dwelling persons with dementia. Methods The study had a descriptive design with a qualitative approach. The primary data source was focus group interviews with purchasers who assess and allocate healthcare services. The interview data were supplemented by a review of administrative decisions made by the purchasers. Data from the focus group interviews were analysed using a descriptive and interpretive approach. Content analysis of the administrative decisions was conducted. Results The purchasers described the allocation process as challenging. The following four themes reflect the complexity of the allocation process: (i) an unfamiliar and unclear concept; (ii) a hierarchy of needs; (iii) an adjusting allocation process; (iv) a challenging documentation of administrative decisions. Conclusions The purchasers viewed a comprehensive allocation process as important. However, a web of different interplaying aspects prevented the purchasers from conducting a comprehensive need-led allocation process. Insufficient assessment or allocation threatens the adequate safeguarding of the psychosocial needs of persons with dementia. Having varied and sufficient services to allocate is of great importance, but is not sufficient. Psychosocial needs must be better incorporated as a significant element throughout the entire allocation process.